К вопросу получения искусственных субстратов - Башкатов, В.Г.; Торохова, О.Н.; Сетт, И.В. (Промышленная ботаника, 2002)
The results of studying the possibility of obtaining the substrate with controllable conditions of soil mineral nutrition are stated, based on properties of ionits of a soil absorbing complex (SAC). It is established, that the soil is capable of the directed formation of SAC kations structure and after some additional researches concerning the regulation of SAC anions structure it furtheron can be used for cultivation of plants with controllable conditions of a mineral nutrition.